Power and Authority in Internet Governance: Return of the State? - Haggart, Blayne; Tusikov, Natasha; Scholte, Jan Aart (Routledge Global Cooperation Series, 2021)
Power and Authority in Internet Governance investigates the hotly contested role of the state in today's digital society. The book asks: Is the state "back" in internet regulation? If so, what forms are state involvement taking, and with what consequences for the future? The volume includes case studies from across the world and addresses a wide range of issues regarding internet infrastructure, data and content. The book pushes the debate beyond a simplistic dichotomy between liberalism and authoritarianism in order to consider also greater state involvement based on values of democracy and human rights. Seeing internet governance as a complex arena where power is contested among diverse non-state and state actors across local, national, regional and global scales, the book offers a critical and nuanced discussion of how the internet is governed – and how it should be governed. Power and Authority in Internet Governance provides an important resource for researchers across international relations, global governance, science and technology studies and law as well as policymakers and analysts concerned with regulating the global internet. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-ND) 4.0 license.